Hosting eSports events: the quality-response-behavioural intentions relationship of eSports fans - Cerqueira, Luís; Ribeiro, Tiago; Cunha de Almeida, Victor Manoel (Frontiers in Sports and Active Living, 2025)
IntroductionThe current study aims to explore how the physical environment of eSports events can influence fan affective responses and their future behavioural intentions. Following the Stimulus-Organism-Response (S-O-R) model, affective response (pleasure) is conceptualized as the organism (mediator) between the physical environment (stimulus) and behavioural intentions (response).MethodThe dependent variables were revisit intention and word-of mouth, while demographic factors including age, education level, nationality, and event attendance to describe the sample and examine their potential influence. Data collection was carried out at a “Lisboa Games Week” event (n = 328) by using a self-administered questionnaire. A Confirmatory Factor Analysis analysed the psychometric properties of the constructs and a subsequent Structural Equation Modelling examined the substantive hypotheses tested.ResultsResults indicate that the physical environment quality positively influences the affective responses of fans, which motivates them to follow eSports events. Furthermore, fans affectively attached to an eSports event are more intent on revisiting it and making word-of-mouth recommendations about it.DiscussionA high standard service quality is a critical issue for event managers, marketeers, and publishers due to its impact on the behavioural and affective value creation towards the event.